Respostas

2014-02-28T15:39:46-03:00
Antes de tudo vamos calcular f(x+h) - f(x):

f(x+h) - f(x) = \frac{1}{x+h} - \frac{1}{x} = \frac{x - (x+h)}{x(x+h)} \\ f(x+h) - f(x) = \frac{x-x-h}{x(x+h)} \Rightarrow f(x+h) - f(x) = \frac{-h}{x(x+h)}

Agora vamos calcular aquela fração:

\frac{f(x+h) - f(x)}{h} = \frac{1}{h}.(f(x+h)-f(x)) \Rightarrow \frac{f(x+h)-f(x)}{h} = \frac{1}{h}.\frac{-h}{x(x+h)}

Se h=0 isso não pode ser calculado, agora se h≠0 temos:

\boxed{\boxed{\frac{f(x+h)-f(x)}{h} = \frac{-1}{x(x+h)}}}